TAFKHĪM AND TARQĪQ OF RĀ’ AND LĀM IN THE RECITATIONS OF ḤAFṢ AND WARSH (A STUDY OF QIRĀ’ĀT AL-QUR’ĀN) - Roihan Nasution, Muhammad (The Department of the Qur'anic Studies, Faculty of Ushuluddin, Adab, and Da'wah, State Institute of Islamic Studies (IAIN) Langsa, 2023)
This article describes and analyses the tafhkīm and tarqīq of rā’ and lām in the recitations of Ḥafṣ and Warsh. It is library study and employs the descriptive-analytical method. The study shows that (1) tafkhīm and tarqīq are discussed in the science of qirā'āt in relation to the rule on the pronunciation of rā' and lām; (2) tafkhīm and tarqīq of rā’ and lām differ between Ḥafṣ and Warsh. This study contributes to the qirā’āt and ʿUlūm al-Qur’ān literature. It removes some doubt among Muslims about the correct pronunciation of both letters, as both recitations indeed were narrated by the Messenger of Allah to his companions by means of mushāfahah. The study may become an essential reference for Muslims in understanding the various methods by which the Qur’ān is recited.